IMPLEMENTATION OF THE TOTAL PHYSICAL RESPONSE (TPR) LEARNING METHOD IN LEARNING ENGLISH IN PRIMARY SCHOOL - Daristin, Pipit Ertika; Rokhim, Arif Nur; Maghfiroh (Bilingua, 2024)
This research aims to describe and explain the implementation of the Total Physical Response (TPR) learning method to develop the speaking skills of third grade elementary school students. This research is a qualitative descriptive study. The subjects of this research were students aged 8-9 years. The techniques used in this research are observation, interviews and documentation. The results of this research describe the implementation of the Total Physical Response (TPR) method in English learning for third grade elementary school students. This research shows the role of the teacher along with the stages of the method in English language learning activities with Total Physical Response, and shows that the total physical response (TPR) method is an appropriate method to use in learning for elementary school students, so it is hoped that its implementation will be developed in different age groups and other aspects of children's development .